2008
DOI: 10.1177/0091270007309703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction Between Voriconazole and Efavirenz at Steady State in Healthy Male Subjects

Abstract: A randomized, placebo-controlled (with respect to voriconazole), 2-period, multiple-dose intragroup fixed-dose sequence study was conducted in 34 healthy male subjects to evaluate the interactions between voriconazole (triazole antifungal agent) and efavirenz (reverse transcriptase inhibitor). In period 1, subjects received 200 mg twice-daily (bid) voriconazole (n = 17) or placebo (n = 17) for 3 days (400-mg bid loading doses on day 1). In period 2, following a 7-day washout, subjects received 400 mg once-dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 26 publications
8
53
0
Order By: Relevance
“…As per the literature, administration of multiple doses of efavirenz results in decreased exposure in humans and animals, suggesting an autoinduction of efavirenz metabolism [29,32,33,36,37]. The plasma half-life of efavirenz in animals is approximately 0.8 to 1.9 h compared to more than 40 h in humans [38,39].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As per the literature, administration of multiple doses of efavirenz results in decreased exposure in humans and animals, suggesting an autoinduction of efavirenz metabolism [29,32,33,36,37]. The plasma half-life of efavirenz in animals is approximately 0.8 to 1.9 h compared to more than 40 h in humans [38,39].…”
Section: Discussionmentioning
confidence: 98%
“…In vitro and in vivo studies demonstrated that efavirenz is a potent inducer of CYP3A4 in a concentration-and time-dependent manner [22,32,33]. Clinical drug-drug interaction studies showed that efavirenz signifi cantly induced CYP enzymes and decreased the concentration levels of several CYP3A4 [34,35] substrates predominantly and, CYP2C9 and CY-P2C19 substrates partly [36]. Enzyme induction has important clinical implications when enhanced drug metabolism results in lower drug concentrations, which leads to a suboptimal effi cacious response or, even worse, the development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although findings from in vivo studies are generally limited, our in vitro data are consistent with the findings of in vivo studies that showed that voriconazole interacts with certain CYP2B6 substrates. Voriconazole has recently been reported to significantly slow the elimination of efavirenz in healthy volunteers (37). Although the authors of that study (37) suggested that CYP3A was the mechanism for this interaction, the available in vitro evidence (9,66) on May 9, 2018 by guest http://aac.asm.org/ efavirenz and that inhibition of CYP2B6 is the main mechanism by which voriconazole increases efavirenz exposure in humans (37).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies and case reports have documented that voriconazole substantially reduces the clearance of several drugs, including warfarin (49), phenytoin (48), midazolam (53), diazepam (52), immunosuppressant drugs (cyclosporine, sirolimus, and tacrolimus) (46,47), efavirenz (37), methadone (36), ibuprofen (27), diclofenac (26), fentanyl and alfentanil (54), oxycodone (22), and omeprazole (47). Considering the mechanisms of clearance of the drugs affected (3), many of these drug-drug interactions appear to be attributable to pharmacokinetic changes that can be understood in terms of inhibition of the cytochrome P450 (CYP) system.…”
mentioning
confidence: 99%
See 1 more Smart Citation